Nilai-Nilai Pendidikan Sosial Dalam Tradisi Kenduri Di Desa Tinggi Ari Kabupaten Kaur - Pratiwi, Delva Ayu; Maryam, Maryam; Yunarman, Sepri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the social education values ​​contained in the kenduri tradition by taking the research area in Tinggi Ari village, Kaur district. The method used is a qualitative method. Data collection techniques used in this study are interviews, observation and documentation. The results of the study indicate that the kenduri tradition is a banquet for the birth of a child as a form of gratitude to Allah SWT. The purpose of this kenduri is to avoid disasters and evil creatures and to ask for the safety of the child to God in order to get safety and health for the newborn child. The process of implementing this kenduri begins with the preparation stage of family deliberation, bejeghum to the community, the stage of bathing the baby using lime, turmeric and kemiling that have been incanted, finally the closing stage continued with eating together. The conclusion of this study is that kenduri is a traditional activity that has the purpose of increasing gratitude to God, strengthening ties between residents, and maintaining and preserving cultural values ​​and mutual cooperation in society. Keywords: Tinggi Ari Village, Social Education Values, Kenduri Tradition